Multiscale Modulation of Nanocrystalline Cellulose Hydrogel via Nanocarbon Hybridization for 3D Neuronal Bilayer Formation. Issue 26 (22nd May 2017) - Kim, Dongyoon; Park, Subeom; Jo, Insu; Kim, Seong‐Min; Kang, Dong Hee; Cho, Sung‐Pyo; Park, Jong Bo; Hong, Byung Hee; Yoon, Myung‐Han
Abstract : Bacterial biopolymers have drawn much attention owing to their unconventional three‐dimensional structures and interesting functions, which are closely integrated with bacterial physiology. The nongenetic modulation of bacterial (Acetobacter xylinum) cellulose synthesis via nanocarbon hybridization, and its application to the emulation of layered neuronal tissue, is reported. The controlled dispersion of graphene oxide (GO) nanoflakes into bacterial cellulose (BC) culture media not only induces structural changes within a crystalline cellulose nanofibril, but also modulates their 3D collective association, leading to substantial reduction in Young's modulus (≈50%) and clear definition of water–hydrogel interfaces. Furthermore, real‐time investigation of 3D neuronal networks constructed in this GO‐incorporated BC hydrogel with broken chiral nematic ordering revealed the vertical locomotion of growth cones, the accelerated neurite outgrowth (≈100 µm per day) with reduced backward travel length, and the efficient formation of synaptic connectivity with distinct axonal bifurcation abundancy at the ≈750 µm outgrowth from a cell body. In comparison with the pristine BC, GO‐BC supports the formation of well‐defined neuronal bilayer networks with flattened interfacial profiles and vertical axonal outgrowth, apparently emulating the neuronal development in vivo. We envisioned that our findings may contribute to various applications of engineered BC hydrogel to fundamental neurobiology studies and neural engineering. Abstract : The judicious incorporation of exogenous nanocarbon flakes into the culture environment effectively modulates bacterial synthesis of nanocrystalline cellulose hydrogel and collective dynamics of bacterial colony association, leading to a novel cellulose hydrogel structure. The resultant well‐manipulated hybrid hydrogel scaffold with planarized surface profiles and homogenous fiber alignment enables the formation of a bilayered 3D artificial neuronal network.